THE ROLE OF SUSTAINABLE DEVELOPMENT IN ECONOMICS: GLOBAL SHIFTS (Journal of Universal Science Research, 2025)
This work is aimed to explore the effects of the “Sustainable Development” agenda on global trends and countries. A collaboration of people and sustainable production was examined by taking one of the goals of sustainable development into consideration: the influence or contribution people can have on improving and developing the sustainability of consumption